MicroRNA‐138 Inhibits Osteogenic Differentiation and Mineralization of Human Dedifferentiated Chondrocytes by Regulating RhoC and the Actin Cytoskeleton. (18th July 2018) - Zheng, Hongjun; Ramnaraign, David; Anderson, Britta A; Tycksen, Eric; Nunley, Ryan; McAlinden, Audrey
ABSTRACT: MicroRNAs (miRNAs) are known to play critical roles in many cellular processes including those regulating skeletal development and homeostasis. A previous study from our group identified differentially expressed miRNAs in the developing human growth plate. Among those more highly expressed in hypertrophic chondrocytes compared to progenitor chondrocytes was miR‐138, therefore suggesting a possible role for this miRNA in regulating chondrogenesis and/or endochondral ossification. The goal of this study was to determine the function of miR‐ 138 in regulating osteogenesis by using human osteoarthritic dedifferentiated chondrocytes (DDCs) as source of inducible cells. We show that over‐expression of miR‐138 inhibited osteogenic differentiation of DDCs in vitro. Moreover, cell shape was altered and cell proliferation and possibly migration was also suppressed by miR‐138. Given alterations in cell shape, closer analysis revealed that F‐actin polymerization was also inhibited by miR‐138. Computational approaches showed that the small GTPase, RhoC, is a potential miR‐138 target gene. We pursued RhoC further given its function in regulating cell proliferation and migration in cancer cells. Indeed, miR‐138 over‐expression in DDCs resulted in decreased RhoC protein levels. A series of rescue experiments showed that RhoC over‐expression could attenuate the inhibitory actions of miR‐138 on DDC proliferation, F‐actin polymerization and osteogenic differentiation. Bone formation was also found to be enhanced within human demineralized bone scaffolds seeded with DDCs expressing both miR‐138 and RhoC. In conclusion, we have discovered a new mechanism in DDCs whereby miR‐138 functions to suppress RhoC which subsequently inhibits proliferation, F‐actin polymerization and osteogenic differentiation. To date, there are no published reports on the importance of RhoC in regulating osteogenesis. This opens up new avenues of research involving miR‐138 and RhoC pathways to better understand mechanisms regulating bone formation in addition to the potential use of DDCs as a cell source for bone tissue engineering. © 2018 The Authors. JBMR Plus is published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.